Economic Attractiveness of Tourism and Hospitality Sphere in Modern Crisis Conditions - Tetiana CHERNYCHKO; Olha MILASHOVSKA; Oksana FEYER; Tetiana SHYTIKOVA; Nadiia HOBLYK-MARKOVYCH; Maryna RUBISH (Communications of International Proceedings, 2020)
The COVID-19 pandemic has posed uncertain challenges for the hospitality sphere and academia, the recognition and solution of which will build a new model for the development of the hospitality industry. The purpose of the article is to substantiate the parameters for assessing the economic attractiveness of tourism and the hospitality sector in crisis conditions (in the context of the COVID-19 pandemic). The research methodology is formed on the basis of system analysis, synthesis and generalization of scientific literature. The theoretical basis of the study was the latest articles and publications of scientists who studied the problem of the development of the hospitality sector in a crisis environment (in the context of the COVID-19 pandemic). It has been determined in the article that the sphere of hospitality encompasses a set of services related to accommodation, meals, transportation, organization of leisure for consumers of services, aimed at meeting their needs as much as possible. It has been substantiated that the economic attractiveness of the hospitality sector is the ability of entrepreneurial structures whose activities are aimed at meeting the demand of customers – consumers of hotel, tourist, excursion, restaurant and other forms and types of business, to ensure a high level of performance and efficiency. It has been concluded that in the context of  worsening epidemic situation and rise in COVID-19 cases, tourism and hospitality enterprises should significantly revise the existing policy of economic attractiveness and change approaches to organizing work with consumers of services.
Keywords: COVID-19; sphere of hospitality; global tourism; economic impact; economic attractiveness.